Pharmacological and electrophysiological characterization of AZSMO-23, an activator of the hERG K+ channel - Mannikko, R (Br J Pharmacol, 2015)
BACKGROUND AND PURPOSE: We aimed to characterize the pharmacology and electrophysiology of N-[3-(1H-benzimidazol-2-yl)-4-chloro-phenyl]pyridine-3-carboxamide (AZSMO-23), an activator of the human ether-a-go-go-related gene (hERG)-encoded K(+) channel (K(v)11.1). EXPERIMENTAL APPROACH: Automated electrophysiology was used to study the pharmacology of AZSMO-23 on wild-type (WT), Y652A, F656T or G628C/S631C hERG, and on other cardiac ion channels. Its mechanism of action was characterized with conventional electrophysiology. KEY RESULTS: AZSMO-23 activated WT hERG pre-pulse and tail current with EC(50) values of 28.6 and 11.2 μM respectively. At 100 μM, pre-pulse current at +40 mV was increased by 952 ± 41% and tail current at −30 mV by 238 ± 13% compared with vehicle values. The primary mechanism for this effect was a 74.5 mV depolarizing shift in the voltage dependence of inactivation, without any shift in the voltage dependence of activation. Structure–activity relationships for this effect were remarkably subtle, with close analogues of AZSMO-23 acting as hERG inhibitors. AZSMO-23 blocked the mutant channel, hERG Y652A, but against another mutant channel, hERG F656T, its activator activity was enhanced. It inhibited activity of the G628C/S631C non-inactivating hERG mutant channel. AZSMO-23 was not hERG selective, as it blocked hK(v)4.3-hKChIP2.2, hCa(v)3.2 and hK(v)1.5 and activated hCa(v)1.2/β2/α2δ channels. CONCLUSION AND IMPLICATIONS: The activity of AZSMO-23 and those of its close analogues suggest these compounds may be of value to elucidate the mechanism of type 2 hERG activators to better understand the pharmacology of this area from both a safety perspective and in relation to treatment of congenital long QT syndrome.